Exercise Therapy versus Pharmacological Management in Nonspecific Chronic Low Back Pain: A Narrative Review of Clinical Evidence and Recommendations - Żukowski, Marcel Artur; Dachowska, Sandra; Haraj, Jan; Bieniek, Maciej; Woźniak, Kinga; Sobkowiak, Marcin; Namysł, Maria; Matczak, Simon (Quality in Sport, 2026)
Chronic non-specific low back pain (NSCLBP) is defined as pain and discomfort lasting at least 12 weeks that cannot be clearly attributed to a specific structural pathology after excluding specific causes of back pain. It is a significant health problem with a major impact on patients’ functioning, reducing quality of life, limiting mobility and increasing the number of comorbidities. NSCLBP is also associated with a higher risk of mortality. This is a global problem, it is estimated that chronic lower back pain affects around 8% of the adult population, providing a therapeutic challenge for physicians of many specialties across several continents. The treatment protocol for NSCLBP includes pharmacological and non-pharmacological interventions, which involve a variety of exercises that differ in terms of difficulty and effectiveness. Exercise-based therapies vary in type, intensity and clinical efficacy, ranging from core stabilization exercises, stretching and strength training to aerobic activities such as walking or swimming. Exercise is a key component in the treatment of NSCLBP, as evidenced by data showing significant reductions in pain and disability. Medication helps with the flare-ups, but cannot replace physical activity when it comes to achieving a genuine, lasting recovery and a return to normal activity.